A Single-Cell Characterization of Human Post-implantation Embryos Cultured In Vitro Delineates Morphogenesis in Primary Syncytialization - Wang, Yiming; Jiang, Xiangxiang; Jia, Lei; Wu, Xulun; Wu, Hao; Wang, Yue; Li, Qian; Yu, Ruoxuan; Wang, Hongmei; Xiao, Zhenyu; Liang, Xiaoyan (Frontiers in Cell and Developmental Biology, 2022)
Implantation of the human blastocyst is a milestone event in embryonic development. The trophoblast is the first cell lineage to differentiate during implantation. Failures in trophoblast differentiation during implantation are correlated to the defects of pregnancy and embryonic growth. However, many gaps remain in the knowledge of human embryonic development, especially regarding trophoblast morphogenesis and function. Herein, we performed single-cell RNA sequencing (scRNA-seq) analysis on human post-implantation embryos cultured in vitro. A hierarchical model was established, which was characterized by the sequential development of two primitive cytotrophoblast cell (pCTB) subtypes, two primitive syncytiotrophoblast subtypes, and migrative trophoblast cells (MTB) after the trophectoderm . Further analysis characterized cytoskeleton transition of trophoblast cells and morphogenesis, such as irregular nuclei, cell cycle arrest, and cellular aging during implantation. Moreover, we found syncytialization of hTSCs could mimic the morphogenesis, serving as a powerful tool for further understanding of the mechanism during the implantation stage of pregnancy. Our work allows for the reconstruction of trophoblast cell transcriptional transition and morphogenesis during implantation and provides a valuable resource to study pathologies in early pregnancy, such as recurrent implantation failure.